A new application of generalized quasi-power increasing sequences - Bor, H. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We prove a theorem dealing with $|\overline{N}, p_n, θ_n|_k$-summability using a new general class of power increasing sequences instead of a quasi-$η$-power increasing sequence. This theorem also includes some new and known results.